2020
DOI: 10.1186/s13018-020-01841-0
|View full text |Cite
|
Sign up to set email alerts
|

Atorvastatin promotes bone formation in aged apoE–/– mice through the Sirt1–Runx2 axis

Abstract: Background: Statins are the most widely used drugs in elderly patients; the most common clinical application of statins is in aged hyperlipemia patients. There are few studies on the effects and mechanisms of statins on bone in elderly mice with hyperlipemia. The study is to examine the effects of atorvastatin on bone phenotypes and metabolism in aged apolipoprotein E-deficient (apoE-/-) mice, and the possible mechanisms involved in these changes. Methods: Twenty-four 60-week-old apoE-/mice were randomly alloc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 53 publications
0
11
0
1
Order By: Relevance
“…Relevant in vitro experiments have shown that statins can inhibit the effect of hormones, upregulate the expression of Cbfa1 (Growth rate compared to group 1: Group3 12%; Group4 19%; Group 26%) and Runx2 (Growth rate compared to group 1: Group3 16%; Group4 21%; Group 29%), and inhibit the expression of PPAR-γ, so as to prevent the fatty marrow cavity, reduce the intramedullary pressure, improve the local blood flow, reduce the cytotoxicity and increase the osteogenesis. 25 , 26 The current research results show that statins can prevent the necrosis of the femoral head and early treatment in animal models or in the human body with a large amount of hormone. However, due to necrosis of the femoral head, 85% of statins are metabolized in the liver, and only 5% of the remaining 15% exist in the blood in a free state, so that few drugs reach the local area.…”
Section: Resultsmentioning
confidence: 83%
“…Relevant in vitro experiments have shown that statins can inhibit the effect of hormones, upregulate the expression of Cbfa1 (Growth rate compared to group 1: Group3 12%; Group4 19%; Group 26%) and Runx2 (Growth rate compared to group 1: Group3 16%; Group4 21%; Group 29%), and inhibit the expression of PPAR-γ, so as to prevent the fatty marrow cavity, reduce the intramedullary pressure, improve the local blood flow, reduce the cytotoxicity and increase the osteogenesis. 25 , 26 The current research results show that statins can prevent the necrosis of the femoral head and early treatment in animal models or in the human body with a large amount of hormone. However, due to necrosis of the femoral head, 85% of statins are metabolized in the liver, and only 5% of the remaining 15% exist in the blood in a free state, so that few drugs reach the local area.…”
Section: Resultsmentioning
confidence: 83%
“…Both in vitro and in vivo studies support that statins, or HMG-CoA reductase inhibitors, promote osteogenesis and bone formation [ 42 ]. Atorvaststin was proven to enhance bone formation in apolipoprotein E-deficient (apoE –/– ) mice by increasing the gene and protein expression of Sirt1 and Runx2 [ 43 ]. Although its association with bone formation was unclear, treatment of adipocytes with avasimibe resulted in significant reduction of lipid accumulation, which is the reciprocal effect of osteogenic differentiation in mesenchymal stem cells [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, statins inhibit osteoclast activation and differentiation [26]. A few preclinical studies have reported the anabolic effects of statins on bone [26,27]. For instance, in an apolipoprotein E-deficient (apoE −/− ) mouse study, atorvastatin administration for as long as 12 weeks increased bone mass and improved bone microarchitecture in trabecular bone and increased the mRNA expression of the serum bone formation marker osteocalcin [27].…”
Section: Discussionmentioning
confidence: 99%